Strategi Pemulihan Ekonomi Nasional di Jawa Timur melalui JATIM BANGKIT - Diana Rapitasari (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
The National Economic Recovery Strategy in East Java is really a plan or map to help leaders or direct organization in East Java in economic recovery efforts, handling the pandemic of Corona Virus Disease (COVID-19) or responding to threats that threaten the economy or financial system as well as economic rescue in East Java. This article was written using a qualitative descriptive method with interview and documentation techniques. The information of this research is officials who are in the Regional Development Planning Agency of East Java Province who are members of the National Economic Recovery Program in East Java through East Java Bangkit, so that the authors can present data systematically, factually and accurately regarding facts in the field. National Economic Recovery Strategies in East Java include recovery of trade and industrial activities, overcoming trade barriers both import duties and import export regulations, budget allocated for health and education in order to ease the burden on society, increase disposable income through creative efforts, encourage household consumption, which is a contributor to aggregate expenditure, continues the subsidy program for small industries and cooperatives as well as optimism for East Java's economic growth.